Financial Relations In The Global Economy - Ibragimov Husan Usmonjon O'g'li (Peerian Journals Publishing, 2025)
The global economy today represents a complex and multifaceted system of economic relations between countries. In this system, financial relations, trade, investments, exchange rates and many other factors work interdependently. The global financial system plays an important role in allocating resources among countries, making investments and stimulating economic growth.
Keywords: global economy; financial resources; financial relations